A System for an Accurate 3D Reconstruction in Video Endoscopy Capsule. (30th November 2009) - Kolar, Anthony; Romain, Olivier; Ayoub, Jade; Faura, David; Viateur, Sylvain; Granado, Bertrand; Graba, Tarik
Abstract : Since few years, the gastroenterologic examinations could have been realised by wireless video capsules. Although the images make it possible to analyse some diseases, the diagnosis could be improved by the use of the 3D Imaging techniques implemented in the video capsule. The work presented here is related to Cyclope, an embedded active vision system that is able to give in real time both 3D information and texture. The challenge is to realise this integrated sensor with constraints on size, consumption, and computational resources with inherent limitation of video capsule. In this paper, we present the hardware and software development of a wireless multispectral vision sensor which allows to transmit, a 3D reconstruction of a scene in realtime. multispectral acquisitions grab both texture and IR pattern images at least at 25 frames/s separately. The different Intellectual Properties designed allow to compute specifics algorithms in real time while keeping accuracy computation. We present experimental results with the realization of a large-scale demonstrator using an SOPC prototyping board.